2004
DOI: 10.1007/s00586-003-0618-8
|View full text |Cite
|
Sign up to set email alerts
|

A new skin-surface device for measuring the curvature and global and segmental ranges of motion of the spine: reliability of measurements and comparison with data reviewed from the literature

Abstract: There is an increasing awareness of the risks and dangers of exposure to radiation associated with repeated radiographic assessment of spinal curvature and spinal movements. As such, attempts are continuously being made to develop skinsurface devices for use in examining the progression and response to treatment of various spinal disorders. However, the reliability and validity of measurements recorded with such devices must be established before they can be recommended for use in the research or clinical envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
242
6
27

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 328 publications
(305 citation statements)
references
References 51 publications
16
242
6
27
Order By: Relevance
“…Thus, the patients had flatter and stiffer lumbar spines than normal. The controls showed mean values for ROF lumbar similar to those reported in the literature for healthy individuals assessed using other skin-mounted motion analysis devices [8, 12,34], double inclinometers [36] or X-ray measurements [44], in part confirming the validity of the measures. Whether the reduced ROF lumbar can be attributed entirely to the results of the disc prolapse, or, rather, was also a factor contributing to its development in the first place, cannot be ascertained from the results of this study.…”
Section: Generalsupporting
confidence: 83%
See 3 more Smart Citations
“…Thus, the patients had flatter and stiffer lumbar spines than normal. The controls showed mean values for ROF lumbar similar to those reported in the literature for healthy individuals assessed using other skin-mounted motion analysis devices [8, 12,34], double inclinometers [36] or X-ray measurements [44], in part confirming the validity of the measures. Whether the reduced ROF lumbar can be attributed entirely to the results of the disc prolapse, or, rather, was also a factor contributing to its development in the first place, cannot be ascertained from the results of this study.…”
Section: Generalsupporting
confidence: 83%
“…1). The intratester and inter-tester, and day-to-day reliability of the Spinal Mouse has been published in previous studies [25,34], in which further details about the system are also given [34]. Briefly, the device is guided along the spine, slightly paravertebrally, from a start position at the spinous process of C7 to an end position at S3.…”
Section: Assessments: Questionnairesmentioning
confidence: 99%
See 2 more Smart Citations
“…To the authors' knowledge, the reliability of this device has not been demonstrated. The Spinal Mouse (Idiag, Voletswil, Switzerland) is a device that contains accelerometers, which measure distance and inclination as it is guided along the length of the spine [33]. A study which evaluated the reliability of the Spinal Mouse demonstrated moderate to good between-day and interexaminer reliability when measuring lumbar and thoracic curvatures [33].…”
Section: Introductionmentioning
confidence: 99%